Differences in cognitive performance and cognitive decline across European regions: a population-based prospective cohort study - Formanek, Tomas; Kagstrom, Anna; Winkler, Petr; Cermakova, Pavla (European psychiatry, 2019)
BACKGROUND: A large variation in cognitive performance exists between European regions. However, it is unclear how older Europeans differ in the rate of cognitive decline. METHODS: We analysed data from 22 181 individuals (54% women; median age 71) who participated in the Survey on Health, Ageing and Retirement in Europe. Cognition was measured using tests on verbal fluency, immediate and delayed recall. We used linear regression and linear mixed effects regression to examine regional differences in the level of cognitive performance and the rate of cognitive decline. RESULTS: Scandinavians had the highest baseline cognitive scores (mean standardized overall cognitive score 0.3), followed by Western Europeans (mean 0.2), Central and Eastern Europeans (mean 0.1) and individuals from Mediterranean countries (mean -0.4). These differences persisted even after adjustment for sociodemographic and clinical characteristics. The annual cognitive decline in Scandinavia (0.59%) was approximately two times greater than in Western Europe (0.28%), Central and Eastern Europe (0.25%) and Mediterranean countries (0.23%). DISCUSSION: There are substantial differences in cognitive performance as well as rates of cognitive decline among the elderly throughout European regions. This might be explained by differing levels of cognitive reserve.
Keywords: senioři; Reserve; Cognitive Dysfunction; Aging; Cognition; Europe; Cohort Studies; lineární modely; Evropa; Cognition Disorders; průzkumy a dotazníky; mužské pohlaví; Prospective Studies; kohortové studie; Change; Geriatric Assessment; kognitivní poruchy; kognice; Linear Models; stárnutí; geriatrické hodnocení; ženské pohlaví; Humans; prospektivní studie; zeměpis; Surveys and Questionnaires; kognitivní dysfunkce; Health Status; Geography; zdravotní stav; Female; Aged; Epidemiology; lidé; Male